2017
DOI: 10.3892/mmr.2017.8036
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates inflammatory damage and protects against osteoarthritis in a rat model of osteoarthritis

Abstract: Resveratrol is a non-flavonoid polyphenol compound with a stilbene structure. As a type of phytoalexin produced under stress in plants, it improves the plant's resistance against pathogens and environment deterioration, and performs important functions beneficial to human health, such as anti-cancer, anti-oxidation, regulating blood lipid levels and prolonging life span. The effects of resveratrol were examined in a rat model of osteoarthritis (OA) and observed to ameliorate inflammatory damage and protect aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 28 publications
2
67
0
Order By: Relevance
“…Besides, RSV alleviated LPS-induced inflammation, as the release of IL-1β, IL-6 and TNF-α was significantly repressed by RSV preconditioning. Consistent with previous studies [14,27,28], these findings suggested the anti-apoptotic and anti-inflammatory functions of RSV on ATDC5 cells and provided evidences that RSV might be a promising therapeutic option for osteoarthritis treatment. It is believed that RSV affects the initiation and progression of many diseases through several mechanisms.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 80%
“…Besides, RSV alleviated LPS-induced inflammation, as the release of IL-1β, IL-6 and TNF-α was significantly repressed by RSV preconditioning. Consistent with previous studies [14,27,28], these findings suggested the anti-apoptotic and anti-inflammatory functions of RSV on ATDC5 cells and provided evidences that RSV might be a promising therapeutic option for osteoarthritis treatment. It is believed that RSV affects the initiation and progression of many diseases through several mechanisms.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 80%
“…Activation of Nrf2 plays an important role in antioxidation and anti‐inflammation mechanisms, while ROS are produced in the course of endogenous cellular oxidation. Data have shown that Res ameliorates inflammatory damage and protects against osteoarthritis in a rat model of osteoarthritis via NF‐κB and HO‐1/Nrf2 signaling . Res might protect rat vascular smooth muscle cells against redox injury induced by calcification through the involvement of the Nrf2 pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Possessing a stilbene structure, resveratrol acts as a non-flavonoid polyphenol compound. It has been proven that resveratrol can make plants more resistant to pathogens as well as improve environment deterioration [6] . Wei et al [6] also revealed that resveratrol could improve the inflammatory damage as well as protect against OA in an OA rat model.…”
Section: Discussionmentioning
confidence: 99%
“…We used CCK-8 kit to measure chondrocytes viability following the instruction of manufacturers. In brief, we seeded human OA chondrocytes in 96-well plates (5×10 5 cells/ml) and treated them with or without resveratrol (6,12,24, 48 μM) for 24h. After that, we added 10 uL CCK-8 into the plates.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation